Potential benefits of minimum unit pricing for alcohol versus a ban on below cost selling in England 2014: modelling study. (30th September 2014) - Brennan, Alan; Meng, Yang; Holmes, John; Hill-McManus, Daniel; Meier, Petra S
Abstract : Objective To evaluate the potential impact of two alcohol control policies under consideration in England: banning below cost selling of alcohol and minimum unit pricing. Design Modelling study using the Sheffield Alcohol Policy Model version 2.5. Setting England 2014-15. Population Adults and young people aged 16 or more, including subgroups of moderate, hazardous, and harmful drinkers. Interventions Policy to ban below cost selling, which means that the selling price to consumers could not be lower than tax payable on the product, compared with policies of minimum unit pricing at £0.40 (€0.57; $0.75), 45p, and 50p per unit (7.9 g/10 mL) of pure alcohol. Main outcome measures Changes in mean consumption in terms of units of alcohol, drinkers' expenditure, and reductions in deaths, illnesses, admissions to hospital, and quality adjusted life years. Results The proportion of the market affected is a key driver of impact, with just 0.7% of all units estimated to be sold below the duty plus value added tax threshold implied by a ban on below cost selling, compared with 23.2% of units for a 45p minimum unit price. Below cost selling is estimated to reduce harmful drinkers' mean annual consumption by just 0.08%, around 3 units per year, compared with 3.7% or 137 units per year for a 45p minimum unit price (an approximately 45 times greater effect). The ban on below cost selling has a small effect on population health—saving an estimated 14 deaths and 500 admissions to hospital per annum. In contrast, a 45p minimum unit price is estimated to save 624 deaths and 23 700 hospital admissions. Most of the harm reductions (for example, 89% of estimated deaths saved per annum) are estimated to occur in the 5.3% of people who are harmful drinkers. Conclusions The ban on below cost selling, implemented in the England in May 2014, is estimated to have small effects on consumption and health harm. The previously announced policy of a minimum unit price, if set at expected levels between 40p and 50p per unit, is estimated to have an approximately 40-50 times greater effect.